2019
DOI: 10.3390/plasma2020015
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Magnetic Field Strength and Geometry on the Deposition Rate and Ionized Flux Fraction in the HiPIMS Discharge

Abstract: We explored the effect of magnetic field strength | B | and geometry (degree of balancing) on the deposition rate and ionized flux fraction F flux in dc magnetron sputtering (dcMS) and high power impulse magnetron sputtering (HiPIMS) when depositing titanium. The HiPIMS discharge was run in two different operating modes. The first one we refer to as “fixed voltage mode” where the cathode voltage was kept fixed at 625 V while the pulse repetition frequency was varied to achieve the desired time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
84
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(90 citation statements)
references
References 43 publications
6
84
0
Order By: Relevance
“…There have been a few investigations on this matter that all agree that the magnetic field plays a significant role in the profile of deposition. We have recently shown that, depending on the stationary magnetic field configuration, HiPIMS deposition may result in a more uniform film thickness than dcMS deposition [31]. Furthermore, Qiu et al [56] showed that the target voltage, magnetic field strength and geometry can affect the shape of the racetrack and the target utilization.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been a few investigations on this matter that all agree that the magnetic field plays a significant role in the profile of deposition. We have recently shown that, depending on the stationary magnetic field configuration, HiPIMS deposition may result in a more uniform film thickness than dcMS deposition [31]. Furthermore, Qiu et al [56] showed that the target voltage, magnetic field strength and geometry can affect the shape of the racetrack and the target utilization.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, it has been demonstrated that a small decrease in the magnetic field strength in the HiPIMS process can lead to a significant increase in the deposition rate in that case [2829]. We have recently reported an increase by a factor of 2 and 2.6 of the HiPIMS deposition rate by 83% and 53% weakening of the magnetic field strength (at racetrack) using vanadium [30] and titanium [31] targets, respectively. Thus, utilizing HiPIMS for the deposition of ferromagnetic material can be very beneficial.…”
Section: Introductionmentioning
confidence: 99%
“…The ionized flux fraction F flux and the deposition rate were measured at 30 mm above the racetrack using a gridless ion meter [82]. For details on the experiments and the magnetic field topology, see Hajihoseini et al [80]. The discharge was generated using a magnetic field configuration denoted C0E0 [80], which indicated that both the center and edge magnets sit next to the back of the cathode target and give the highest magnetic field strength (parallel to the target surface) in the cathode target vicinity just above the target racetrack.…”
Section: Discharges and Model Inputsmentioning
confidence: 99%
“…The EEDF is discretized using non-equal energy intervals [38] between 0 eV and a value above the energy that corresponds to the sheath voltage eV SH . The secondary electrons are injected into the discharge volume at an [80], the IRM fitting parameters [31], and the energy discretization parameters for OBELIX. energy close to the energy corresponding to the sheath voltage…”
Section: Discharges and Model Inputsmentioning
confidence: 99%
“…[71]. Several published works have tried to address this problem by modifying the magnetic field strength and orientation of either the magnetron or that of an external magnetic field [74][75][76][77][78]. Another simpler way to increase the deposition rate in HiPIMS is to modify the pulse parameters, e.g.…”
Section: Ion Energy Distribution Function (Iedf)mentioning
confidence: 99%